Biological correlates of P300 and extraversion relationship - Tatalović Vorkapić, Sanja (2009)
Abstract: Because of the great sensitivity of P300 determined in prior research, the aim of this study was to investigate the mediate impact of some biological determinants of P300 on its relationship with extraversion. The sample consisted of 54 female psychology students, right-handers, in the age range of 19–23 years. The P300 was measured by visual oddball paradigm in two trials using EMG/EP device Medelec/TECA SapphireII, 4E. Results showed that those subjects who had glasses, drink coffee, do not take any medications and do not smoke showed significant negative correlation between P300-latency and extraversion. Only those subjects who had glasses showed significant negative correlation between P300-amplitude and extraversion. Also, there were differences between those group subjects in P300-amplitude regarding measuring trial. So, it was concluded that findings have confirmed expected great sensitivity and variability in P300 that mediate its relationship with extraversion and should be controlled in future studies
Bibliografija: 100 jed
Sažetak
Keywords: P300 -- Ekstraverzija -- Biološki korelati